Analisis Kuantitatif Relasi Patron dalam Organisasi Mahasiswa DEMA FTIK UIN Palangka Raya - Rinaldi, Arjuna; Surawan, Surawan (YASIN, 2025)
The relationship between seniors and juniors in student organizations often forms a patronistic pattern that, on one hand, can lead to dependency but, on the other, may function as a constructive mentoring mechanism. This study aims to describe the forms of patron relations in senior-junior dynamics and their impact on the cadre formation process and character development of organizational members. Using a descriptive quantitative approach, data were collected through questionnaires distributed to eighteen respondents and informal interviews with two active members of DEMA FTIK UIN Palangka Raya, 2025/2026 administration. The results indicate that patron culture is predominantly perceived as a form of guidance, empowerment, and moral support from seniors to juniors. This relationship contributes to strengthening the character of cadres in areas such as responsibility, discipline, and initiative, although indications of dependency in decision-making processes were still observed. These findings align with James C. Scott’s patron-client theory, which emphasizes reciprocal relationships marked by positional inequality. This study contributes to the development of cadre formation strategies grounded in equality, participation, and empowerment within student organizations.